A Proposal for a New Arteriovenous Malformation Grading Scale for Neuroendovascular Procedures and Literature Review - Feliciano, Caleb E.; de León Berra, Ramón; Hernández Gaitán, Manuel S.; Rodríguez Mercado, Rafael (Puerto Rico Health Sciences Journal, 2010)
Background: Traditionally, decisions regarding treatment and outcomes for patients with cerebral arteriovenous malformations (AVM) have made use of the Spetzler-Martin grading scale. The latter has withstood the test of time in clinical practice for AVM patients managed surgically and even when comparing studies involving other modalities of treatment. Recent awareness on the applicability of the grading system for risk assessment and outcome determination in cases of treatment by neuroendovascular means has emerged. We propose a preliminary grading system for neuroendovascular procedures based on a revision of the available literature. Methods: A literature search using the keywords ‘arteriovenous malformation’, ‘embolization’ and ‘outcome’ was done. Articles studying the factors involved in complications and outcome determination for endovascular cerebral AVM patients were reviewed. These were tabulated and those dealing with anatomical, radiological and hemodynamic descriptions that were noted as significant determinants of risk or clinical outcome were used for development of a preliminary grading system to be used in a follow-up validation study. Results: A grading system similar to the Spetzler-Martin grading scale was developed using factors deemed in the literature as significant determinants of outcome. The classification includes the number of feeding vessels into the AVM, the eloquence of adjacent areas, and the presence of fistulous components. Follow-up study is underway at our institution to validate our proposal. Yet, significant evidence exists in the literature validating those factors as stand alone determinants of outcome and risk, suggesting that this grading scale may well be applicable to endovascular embolization procedures. Conclusions: A grading scale similar to the Spetzler-Martin grading system for use in risk assessment and outcome determination in brain AVM patients treated by endovascular techniques seems adequate and clinically feasible. Studies on applicability and validation are underway.